Assessing agricultural drought for Binh Thuan province under climate change scenario - Vinh, Phạm Quang; Hương, Phạm Thị Thanh (Vietnam Journal of Earth Sciences, 2013)
Climate change has been a great challenge to human kind. It puts a big stress on various aspects of the economy. One of the issues that recently emerged is agriculture drought. It is a great significance that we can assess the current status of this kind of drought, as well as predict the drought trends in the future. In this paper, the authors used meteorological data (50 years)  from 13 rain gauges in Binh Thuan province to calculate MI (Meteorology Index) by FAO formula in combination with the climate change scenario for the province. There are 4 degrees of drought for current time by calculation (less drought, moderate drought, severe drought, extreme drought) and we can use the same scale for future time such as 2030, 2050 and 2100 by climate change scenario published by Ministry of Resources and Environment in 2009. The results of analyzing data from 1961 to 2010 showed that Tuy Phong district  was mostly extreme drought and Bac Binh district and a part of Phan Thiet city were severe drought. The half of province’s area will be severe - extreme drought in 2050 and two-thirds of province's area in 2100 by climate change scenario.